The Convergence of Online Customer Reviews and Celebrity Endorsements: An Effective Strategy to Enhance Repurchase Intention for Tupperware Products - Rista Nurfajrianti; Innocentius Bernarto (Universitas Pelita Harapan, 2025)
In today’s digital era, online customer reviews and celebrity endorsements significantly influence consumer decisions, especially regarding repurchase intentions. This study explores their roles in shaping Tupperware customers repurchase intentions in Indonesia, addressing the limited empirical research on this topic. A Non-Probability Purposive Sampling method was used to survey 200 Tupperware users. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 software. Out of nine tested hypotheses, eight were accepted, and one was rejected. The results demonstrate that online customer reviews have a significant positive impact on repurchase intention, underscoring their critical role in influencing consumer behavior. Customers are increasingly reliant on digital feedback, which plays a more pivotal role than traditional marketing in driving loyalty. These findings offer valuable insights into Tupperware’s management. By strategically leveraging online reviews and celebrity endorsements, they can optimize promotional campaigns, strengthen customer engagement, and boost brand loyalty in Indonesia’s competitive market. This research emphasizes the importance of integrating digital feedback and influential figures into marketing strategies to enhance repurchase intention, contributing to the broader understanding of consumer behavior in the context of modern marketing.